71+[5x+(-2x+3)]= 25-[-(3x+4)-(4x+3)]
Respuestas a la pregunta
Contestado por
10
Respuesta:
3
Explicación paso a paso:
71-5x-2x+3=25+3x+4+4x+3
71+3-25-4-3=3x+4x+5x+2x
42=14x
x=3
Contestado por
14
Respuesta:
x = 21 / 2
Explicación paso a paso:
71+[5x+(-2x+3)]= 25-[-(3x+4)-(4x+3)]
71+[5x-2x+3]= 25-[-3x-4-4x-3]
71+[3x+3]= 25-[-7x-7]
71+3x+3 = 25 +7x +7
3x+74 = 7x +32
3x - 7x = 32 - 74
-4x = -42
x = (-42) / (-4)
x = 21 / 2
Otras preguntas
Exámenes Nacionales,
hace 6 meses
Exámenes Nacionales,
hace 6 meses
Salud,
hace 11 meses
Matemáticas,
hace 1 año